HUBUNGAN LITERASI KESEHATAN TERKAIT AKTIVITAS FISIK DENGAN KONTROL GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA UPTD PUSKESMAS LEMITO - Polumbato, Djordiyanto; Zainuddin, Zainuddin; Mursyidah, Andi; Hadjarati, Hartono (Medical and Health Journal, 2025)
The incidence of chronic diseases continues to increase across the country as a result of transformation, demographics, and epidemiological. Diabetes mellitus (DM) is one of the chronic diseases that not only causes premature death worldwide but also causes many other complications. The World Health Organization (WHO) predicts that the number of deaths associated with DM will be enhanced by 2030. This quantitative research used a Cross-Sectional research design. The population and the sample in this study were 39 patients suffering from type 2 Diabetes Mellitus in the Puskesmas Lemito working area from January to August 2024, which was taken using the total sampling technique. This study used a questionnaire as an instrument. The data in this study was analyzed using the Fisher exact test. The analysis obtained a p-value = 0.000, which indicated a relationship between health literacy related to physical activity and blood sugar control in type 2 diabetes mellitus patients in the UPTD Lemito working area, Pohuwato Regency.